2016
DOI: 10.1177/0022022116670513
|View full text |Cite
|
Sign up to set email alerts
|

How Does Framing Strategy Affect Evaluation of Culturally Mixed Products? The Self–Other Asymmetry Effect

Abstract: The article examines the effect of bicultural framing strategy on the evaluation of culturally mixed products (CMPs). Across two experiments, we demonstrate a self–other asymmetry effect in the CMP evaluation. Specifically, we examine the “foreign-culture home-culture” strategy in which the foreign culture “modifies” the home culture. This phenomenon leads to less favorable evaluation of CMPs relative to the “home-culture foreign-culture” strategy in which the home culture “modifies” the foreign culture. Furth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
33
0

Year Published

2017
2017
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(34 citation statements)
references
References 13 publications
1
33
0
Order By: Relevance
“…This can range from simultaneous co‐presentation of distinct cultural elements (without actual contact between them) to actual overlap between them (superimposition), in which two cultural representations are occupying the same space or entity, yet maintain their distinct and identifiable characteristics (e.g., a McDonald's restaurant at the Great Wall of China) (Yang, Chen, Xu, Preston, & Chiu, ). The most complete and integrated form of culture mixing is reflected by culture fusion , in which features of distinct cultural representations are mixed together to create a new entity simultaneously possessing features of its different cultures of origin (Cheon, Christopoulos, & Hong, ; Cui, Xu, Wang, Qualls, & Hu, ). Possibly the most widely studied form of culture mixing to date has been simultaneous presentation, which also has been referred to as joint presentation, side‐by‐side presentation, or cultural co‐presence (Chen et al., ; Cheng, Leung, & Wu, ; Chiu et al., ; Morris, Mok, & Mor, ; Peng & Xie, ; Torelli, Chiu, Tam, Au, & Keh, ).…”
Section: Culture Mixing As Cultural Diversitymentioning
confidence: 99%
See 3 more Smart Citations
“…This can range from simultaneous co‐presentation of distinct cultural elements (without actual contact between them) to actual overlap between them (superimposition), in which two cultural representations are occupying the same space or entity, yet maintain their distinct and identifiable characteristics (e.g., a McDonald's restaurant at the Great Wall of China) (Yang, Chen, Xu, Preston, & Chiu, ). The most complete and integrated form of culture mixing is reflected by culture fusion , in which features of distinct cultural representations are mixed together to create a new entity simultaneously possessing features of its different cultures of origin (Cheon, Christopoulos, & Hong, ; Cui, Xu, Wang, Qualls, & Hu, ). Possibly the most widely studied form of culture mixing to date has been simultaneous presentation, which also has been referred to as joint presentation, side‐by‐side presentation, or cultural co‐presence (Chen et al., ; Cheng, Leung, & Wu, ; Chiu et al., ; Morris, Mok, & Mor, ; Peng & Xie, ; Torelli, Chiu, Tam, Au, & Keh, ).…”
Section: Culture Mixing As Cultural Diversitymentioning
confidence: 99%
“…Other patterns of culture mixing more explicitly imply an intrusive presence or “invasion” of one culture by another, such as superimposition and fusion. Compared to less intrusive forms of culture mixing (e.g., simultaneous presentation), superimposition and fusion may risk predominantly more exclusionary reactions to culture mixing based on perceptions of symbolic threat and contamination of one's own culture by foreign or outgroup elements (Cheon et al., ; Cui et al., ; De Keersmaecker et al., ; Yang et al., ).…”
Section: Culture Mixing As Cultural Diversitymentioning
confidence: 99%
See 2 more Smart Citations
“…Consequently, cultural mixing may be tolerated and even encouraged when aspects of one’s own culture are perceived to be spreading and being adopted by other cultures, thereby bolstering the perceived legitimacy or relative status of one’s own worldview. Recent research has indeed demonstrated support for this pattern in the domain of culturally mixed consumer products (Cui, Xu, Wang, Qualls, & Hu, 2016). Similarly, status asymmetries between cultures that are being mixed may also play an important role.…”
Section: Implications and Future Directionsmentioning
confidence: 89%